DIFFERENCES IN STUDENTS’ ATTITUDES TOWARD COMMUNICATION SKILLS IN A MEDICAL SCHOOL IN INDONESIA - Farah Noya; Stazia Noija; Amanda Manuputty (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Communication skills play an important role in clinical practice. Attitudes toward medical communication skills   that are built since a stage of medical student, would affect practice as a doctor later.  Good communication skills based on positive attitude will improve other clinical skills that are needed as a doctor, also will help a doctor to consider the importance of the improvement of the skills quality related to it. A number of studies have explored this context widely using CSAS as an instrument that consists of 2 subscales, a positive (PAS) and a negative (NAS) subscale. This study aimed to determine the difference in attitudes among students in Faculty of Medicine Pattimura University Ambon toward medical communication skills. Method: This was a cross-sectional analytical study that used primary data, obtained using an Indonesian version CSAS questionnaire that is first validated, thus, the scale consists of 24 items within 13 items as PAS and 11 items as NAS. Subjects were 124 active students of the academic year 2014/2015, woh undergo pre-clinical (semesters 2, 4, 6 and 8) and clinical study (Co Ass), obtained through stratified random sampling and complied the restriction criteria. Data were analysed using Mann-Whitney, Kruskall-Wallis, Unpaired t-test, One-Way ANOVA, and Post-Hoc Bonferroni tests with significance level of p<0,05.  Results: There were no difference in attitude toward communication skills between students across most variables; however, there were differences in negative attitudes (NAS) on medical communication skills between each batch of students (p=0.02).Conclusion: The difference in attitude toward communication skills can be seen between students across study batch in Pattimura University Faculty of Medicine.